المحدد الديني للحضارة والسياسات العالمية: قراءة في منظور الفاروقي للعلاقات الدولية: The Religious Determinant for Civilization and Global Policies: A Reading of Al-Faruqi's Perspective on International Relations - عبد العالي, عبد القادر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2013)
يعرض البحث منظور إسماعيل الفاروقي لدور الدين في السياسات العالمية الراهنة، ويرسم ملامح نظرية معيارية في العلاقات الدولية، بناءً على رؤيته لمفهوم التوحيد وما وراء الدين كما ظهرت في عدد من كتبه، لا سيما كتاب التوحيد ومضامينه، وكتابه الإسلام ومشكلة إسرائيل، فقد بين الفاروقي أنَّ الإسلام يقدم حلاًّ للمشكلات العالمية المرافقة لأسس النظام الدولي الراهن، القائم على الإثنية المركزية الغربية، التي تتناقض مع مقتضيات المجتمع العالمي الذي يتسم بالانفتاح والحرية والتعايش. This paper presents the perspective of Ismail al-Faruqi on the role of religion in current international politics, and lays out the features of a normative theory in international relations based on his view of the concepts of Tawhid and meta-religion as presented in a number of his books, particularly "Tawhid: Implications for Thought and Life" and "Islam and the Problem of Israel." Al-Faruqi elucidates how Islam offers solutions to global problems associated with the foundations of the current international system, which is based on the ethno-Euro-centricity, a system that contradicts the needs of the global society, which in turn is characterized by openness, freedom, and coexistence.